2022
DOI: 10.1371/journal.pone.0278965
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine causes neuronal leptin resistance and endoplasmic reticulum stress

Abstract: Abnormally high serum homocysteine levels have been associated with several disorders, including obesity, cardiovascular diseases or neurological diseases. Leptin is an anti-obesity protein and its action is mainly mediated by the activation of its Ob-R receptor in neuronal cells. The inability of leptin to induce activation of its specific signaling pathways, especially under endoplasmic reticulum stress, leads to the leptin resistance observed in obesity. The present study examined the effect of homocysteine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Additionally, PLP acts as a vital mediator in the homocysteine degradation pathway, which involves breaking down homocysteine, an amino acid derived from methionine metabolism. It is essential for maintaining normal homocysteine levels in the body, as elevated levels have been associated with various health issues, including obesity ( Preninka et al 2022 ). Furthermore, excessive consumption of sweets, desserts, and unhealthy fats, particularly those high in refined sugars, often lacks essential nutrients like vitamins B6, thiamin, and folate.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, PLP acts as a vital mediator in the homocysteine degradation pathway, which involves breaking down homocysteine, an amino acid derived from methionine metabolism. It is essential for maintaining normal homocysteine levels in the body, as elevated levels have been associated with various health issues, including obesity ( Preninka et al 2022 ). Furthermore, excessive consumption of sweets, desserts, and unhealthy fats, particularly those high in refined sugars, often lacks essential nutrients like vitamins B6, thiamin, and folate.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 Although the role of Hcy in gestational leptin resistance has not been investigated, results from in vitro models have shown that increased Hcy levels reduce the response to leptin signaling in individuals with obesity. 11 These findings suggest that Hcy could regulate leptin resistance during pregnancy. The relationship between Hcy and leptin has been widely investigated under obstetric conditions with a greater cardiovascular risk; 12 however, contributions of biochemical and hematologic factors in the early modulation of leptin and Hcy levels is not completely understood under physiologic conditions.…”
Section: Introductionmentioning
confidence: 94%
“…Epidemiological studies have indicated that changes in folic acid and methionine metabolism are closely associated with increased levels of homocysteine (Hcy), which induces a proatherogenic response and significantly increases the risk of cardiovascular diseases 9,10 . Although the role of Hcy in gestational leptin resistance has not been investigated, results from in vitro models have shown that increased Hcy levels reduce the response to leptin signaling in individuals with obesity 11 . These findings suggest that Hcy could regulate leptin resistance during pregnancy.…”
Section: Introductionmentioning
confidence: 99%